AGRIBUSINESS APPROACH AND DEVELOPMENT STRATEGY OF CORN (ZEA MAYS) TO MAINTAIN FOOD SECURITY IN KEDIRI REGENCY - Novi Haryati; Arif Wahyu Setiawan (Socio-Economics/Agribusiness Department, 2017)
Corn has a strategic role in Indonesia because it has multipurpose functions such as as food, catle feed and industrial raw materials. The purpose of this study is to analyze: (1) base and non-base area of corn production in Kediri, (2) characteristic of corn farm management in Kediri, (3) the strategies to support food security in Kediri. Data used are primary data collected from farmers and also secondary data from the local government. Primary data was obtained through interviews of 30 respondents of farmers. Secondary data are collected from statistical bureau of Kediri Regency. The methods used are LQ and SWOT. The results show that the basic region of corn are Papar, Plemahan, Plosoklaten, Purwoasri and Pare. Farm management weaknesses in term of agribusiness activities are in the aspect of marketing and processing; however, supported sub-system in agribusiness has played important role in gaining benefit in the whole agribusiness system. According to SWOT analysis, farmers and government need to take advantages of the region strength to gain more opportunities. Improving more innovation on corn based-food production is also important to be induced more.